The practical past and the usefulness of historiography in Xenophon - Bantim de Assumpcao, Luis Filipe (Romanitas - Revista de Estudos Grecolatinos, 2023)
Even today, many researchers try to understand Hellenic historiography in terms of contemporary Western interests, committed to the demands of a scientific History. However, when we analyze Xenophon’s writings, we find that there is no clear and well-marked border between what is historiography and what is not. To this end, we mobilized the concept of practical past, in accordance with the studies of Hayden White, to think about Xenophon’s historiography through the bias of its usefulness in the polis. In this way, Xenophon sought to develop texts that, when disseminated along to its intended recipient, would have practical feasibility amongst Hellenic communities that were inserted in constant conflict scenarios through the 4th Century.